The sleep quality of Medical students: A systematic review (Research, Society and Development, 2024)
The importance of sleep quality and its benefits have been studied since ancient times; Hippocrates, for example, considered the father of medicine, stated that lack of sleep is correlated with boredom, generating physical and mental exhaustion in human beings. Therefore, in the 21st century, it can be said that sleep is a normal physiological state and effectively contributes to reestablishing the organism's hemostatic process, encompassing: thermoregulation, cerebral energy metabolism, memory solidification and binocular vision. Therefore, it is recommended that a young adult sleep around seven to nine hours a night for the benefits of sleep to be effective. However, medical students have difficulty maintaining this daily routine, as they are subjected to an extensive workload, participating in classes in all shifts (morning, afternoon and night). It is worth mentioning that in addition to the daily activities of the college, students, in search of good academic and professional training, participate in academic leagues, internships, tutoring and scientific initiation, which increases stress and overload. Therefore, the general objective of this study is to evaluate the quality of sleep and the sleep-wake pattern of medical students, based on a systematic literature review. The study concluded that the majority of medical students have, in addition to poor sleep quality, a poor quality of life with several stressors that contribute to this reality.